Training on Making Environmentally Friendly Clean Water Filters Using Used Bottles for Residents of Tegallega Village in Cianjur Regency - Rina Rindiani (Research Collaboration Community (RCC), 2021)
Tegallega Village, Warung Kondang District, Cianjur Regency has a problem regarding the availability of clean water, the water used by residents comes from the Cimanceuri River or dug wells where the water is relatively cloudy, even though the use of dirty water has the potential to cause various health problems, such as cholera, dysentery, typhus, and tuberculosis and other diseases. The availability of clean water has always been one of the characteristics of community welfare. How not without clean water it is impossible to realize a prosperous society, a physically and mentally healthy society as a form of participation in developing public health. This activity method in community service uses a follow-up study method with a participatory approach in community service, the team conducts training on how to make simple water filtration that can be used as a source of clean water for families by using plastic bottle waste and other environmentally friendly materials that residents can find around environment in making the dirty water filter. The results of this Community Service Activity went smoothly and were greeted with great enthusiasm by the residents because the practice of making water purification equipment made with materials such as pebbles, coconut fiber, charcoal, fibers, and sponges functioned well from the water which was originally colored cloudy turns to be clearer and odorless.